Laparoscopic management of ectopic pregnancies at unusual sites - Kumar, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ruptured ectopic pregnancies are the most common life threatening emergencies in the obstetrical practice. The tubal ectopics are the most common, but increasing infertility treatments and ART procedures may lead to a rise in the other sites of ectopic also. In the first case of ectopic pregnancy in the ampullary region, the tube was forming a TO Mass and salpingectomy of this damaged tube was not possible because of the adhesions all around and hence ectopic was removed after salpingostomy. The second case with ectopic in the isthmic region with impending rupture was dealt with salpingectomy. The third a cornual pregnancy presented with severe anemia and peripheral vascular collapse, and the ectopic was removed after cornustomy. The fourth case of an ovarian pregnancy again presented with pain abdomen and hemodynamic instability and ovariectomy with removal of the ectopic and some ovarian tissue was done. Ruptured ectopics with their varied and unexpected presentation are great challenges for the minimal invasive procedures in a hemodynamicaly unstable patient. Advancement in the diagnostic and minimal invasive techniques has led to a rapid decline in the mortality and morbidity in such cases. The purpose of reporting these cases are to show the varied and life threatening presentations of these ectopics in unsuspected patients.